Dampak BI 7-day reverse repo rate dan Fed rate terhadap Indeks Saham Syariah Indonesia dengan pendekatan Vector Error Correction Model - Uma'iyah, Auliya Dwi Faisatun; Nurhadi, Bayu (Journal of Economics Research and Policy Studies, 2024)
This research aims to determine how the BI 7-Day Reverse Repo Rate and FED Rate variables influence ISSI movements in the short and long term. This research uses a quantitative approach, namely the Vector Error Correction Model. The data used in this research is secondary data. In the short term, the BI 7-Day Reverse Repo Rate does not affect ISSI, while the FED Rate has a negative effect on ISSI. In the long term, the BI 7-Day Reverse Repo Rate has a positive effect, while the FED Rate has a negative effect on ISSI.